Memória e identidade institucional: inventário do acervo da Escola de Agronomia do Nordeste (1934-1968) - Souza, Katiane da Cunha (2018)
The establishment of the School of Agronomy of the Northeast, in Areia, in the State of Paraíba, rests on a chain of political, economic and socio-cultural factors that, in the national, state and municipal context, came together for its creation in 1934. First lay educational institution superior of Paraíba, existed as an isolated institution until 1968, when it became part of the Federal University of Paraíba. This research is based on the assumption that the value of an institution's memory lies in its generative capacity to subsidize the present, to point out ways, to indicate perspectives of study, to reveal contexts and intentionalities, and to express the culture of a community. It aims to re - signify the memory of the School of Agronomy of the Northeast, from its documentary sources, with a view to the elaboration of an inventory of its collection, at the intersection 1934-1968. It is anchored in a theoretical contribution that favors the categories of memory and institutional identity, in the light of classic and current authors such as Nora (1993), Bosi (1995), Le Goff (2003), Ricoeur (2007), Halbwachs (2009) and Thiesen (2013). It feeds on the historiographical method based on Arostegui (2006) and Vergara, (2010). It is a descriptive study of an exploratory and qualitative nature. It is characterized as a bibliographical and documentary research, privileging, as far as possible, original sources that can put the researcher and the community in contact with the history. Data collection was carried out in Campus II of the Center of Agrarian Sciences of the Federal University of Paraíba, privileging the following places of memory: Archive, Library, Directorate, Coordination of Agronomy and Squares. The findings point to the delimitation of three important moments that imply plural identity to the School of Agronomy of the Northeast: the first, from its creation in 1934, to federalization in 1950, granting it identity as a Research Center and Experimental Agricultural Station. The second includes the 1950s, when the Extension activities were increased, with emphasis on the Ruralista Fairs and the creation of the Domestic Crafts Centers for Women. The third covers the 1960s until its integration with the UFPB in 1968, when teaching stood out in relation to the other activities. As a result, we organize the Institution's documents in an inventory format, with the aim of preserving, disseminating and re-meaning their memory. Our scope is to convert this study into a practical aid for the recognition of the Institution, which goes beyond the internal scope of the academy, recomposes the history of higher education in Paraíba and reveals science as a collective domain. The inventory resulting from this work is a starting point for an effective intervention in the collection of the School and a pioneering instrument for new research on the history, memory and identity of the Institution, Higher Education in Paraíba and Agricultural Education in Brazil.